SPONTANEOUS DISSECTION OF CORONARY ARTERY AS A CAUSE OF ACUTE MYOCARDIAL INFARCTION - E. A. Protasova; N. V. Furman; I. V. Titkov; A. O. Oleynik; K. V. Gusev (Кардиоваскулярная терапия и профилактика)
Spontaneous dissection of coronary arteries (SDCA) is a rare cause factor for acute myocardial infarction. The data provided is modern on the prevalence of SDCA, its predisposing factors as the data on diagnostics and treatment of SDCA. The case described of the myocardial infarction due to SDCA in 34-year old male.